Kreativitas, Gaya Kepimpinan dan Kompetensi dalam Membentuk Kepuasan Kerja Karyawan - Onny Juwono; Yuliana Wangsadinata (Bina Nusantara University, 2010)
The purpose of this research is to analyze the influence of creativity, leadership style, and competence on employee job satisfaction. The method used in this study is the Pearson Correlation, Multiple Regression, and Path Analysis. Data obtained from the employee appraisal by filling in the questionnaire that has been provided by using a Likert scale. The results achieved in this research is creativity (0.828), leadership style (0.962) and competence (0.946) has a strong correlation with employee job satisfaction. It is expected that the results of this research can provide input for PT Interdata Bhakti Mulya in general and leadership in particular so as to improve the performance of the company in years to come.